APLIKASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI SDIT FATHONAH BATURAJA TIMUR - Dazua (UNISAN JURNAL, 2023)
The application of counseling guidance in fostering student morals is an educational process that focuses on changing the morals and behavior of students to behave well and have good morals. The application of counseling guidance in moral development for students at SDIT Fathonah Baturaja has been carried out well. Guidance and Counseling are inseparable activities. The word Guidance is always coupled with Counseling as a compound word, Counseling which is one of the Guidance techniques is often said to be the core of all services and Guidance. Methods of data collection is done by using the method of observation, interviews and documentation. In the analysis carried out the steps of data reduction, data presentation and drawing conclusions. As for analyzing by way of inductive thinking. Based on the data obtained, the results of the research on the Application of Counseling Guidance in the Moral Development of Students at SDIT Fathonah Baturaja show a fairly good and significant level of change, seen from students always following guidance and counseling and moral development using methods of understanding, advice, motivation, advice and habituation. So that slowly can change the nature and habits of students for the better.